Rewarding Work: Cross-National Differences in Benefits, Volunteering During Unemployment, Well-Being and Mental Health. (February 2018) - Kamerāde, Daiga; Bennett, Matthew R
Owing to increasing labour market flexibilization, a growing number of people are likely to experience unemployment and, as a consequence, lower mental health and well-being. This article examines cross-national differences in well-being and mental health between unemployed people who engage in voluntary work and those who do not, using multilevel data from the European Quality of Life Survey on unemployed individuals in 29 European countries and other external sources. This article finds that, regardless of their voluntary activity, unemployed people have higher levels of well-being and mental health in countries with more generous unemployment benefits. Unexpectedly, the results also suggest that regular volunteering can actually be detrimental for mental health in countries with less generous unemployment benefits. This article concludes that individual agency exercised through voluntary work can partially improve well-being but the generosity of unemployment benefits is vital for alleviating the negative mental health effects of unemployment.